IMPROVEMENT OF TEACHING GEOMETRY BASED ON PEDAGOGICALSYNERGETICAL PRINCIPLES - Nazarovich, Dushabaev Olimjon; Khamidovich, Turdibaev Dilshod; Xazratkulovich, Mirmukhamedov Juman; Abduraimovich, Zokirov Abdunazar (International Journal of Psychosocial Rehabilitation, 2020)
Purpose. The purpose of this article is to develop a pedagogical model for implementing the principles of pedagogical synergy in the process of teaching students to solve practical issues in the process of teaching geometry to students of secondary schools, developing their ability to solve practical issues from the point of view of stereometry and conduct in-depth and purely logical research. Methodology and methods. Research on a scientific article, analysis of educational and methodological works, pedagogical experience and observation methods, questionnaires, tests, interviews, mathematical and statistical analysis. Results and scientific novelty. a) created methods for developing students’ logical abilities when teaching them to solve practical problems in stereometry; b) created the principles of pedagogical-synergetic approach to the content of geometric education; c) created methods for using the principles of pedagogical-synergetic approach to solving problems in stereometryа. Practical importance. In total, 100 students were involved in 10-11th grades of secondary schools in accordance with the methodological recommendations given in this article, a check of pedagogical experience was organized and a mathematical and statistical analysis was carried out. As a result of the analysis, it turned out to be effective to implement the principles of the pedagogical-synergetic approach in the geometry presented in this article.